Sustainability-related communication and its influence on competitiveness of companies in the chemical industry - Hyršlová, Jaroslava; Tomšík, Pavel; Vnoučková, Lucie; Hájek, Miroslav (Mendelova univerzita v Brně, 2016)
Interests of companies in sustainability-related communication have risen considerably in recent years. This can be seen not only in the content of corporate annual reports, but also in the number of papers published in scientific journals. This paper focuses on the current state of sustainability-related reporting in chemical industry companies registered in the Association of Chemical Industry in the Czech Republic. It deals with the form and the content of reporting, the importance of different stakeholders in this process as well as benefits of sustainability-related communication and its impacts on competitiveness of the company.
Komunikace o udržitelném rozvoji a její vliv na konkurenceschopnost podniků chemického průmyslu
Keywords: sustainability-related reporting; competitiveness; chemical industry; reporting o udržitelném rozvoji; konkurenceschopnost; chemický průmysl